2017
DOI: 10.1016/j.neuroimage.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparing test-retest reliability of dynamic functional connectivity methods

Abstract: Due to the dynamic, condition-dependent nature of brain activity, interest in estimating rapid functional connectivity (FC) changes that occur during resting-state functional magnetic resonance imaging (rs-fMRI) has recently soared. However, studying dynamic FC is methodologically challenging, due to the low signal-to-noise ratio of the blood oxygen level dependent (BOLD) signal in fMRI and the massive number of data points generated during the analysis. Thus, it is important to establish methods and summary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
166
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(188 citation statements)
references
References 79 publications
10
166
2
Order By: Relevance
“…The network metrics include clustering coefficient, characteristic path length, local efficiency, global efficiency, modularity, hierarchy, and degree, and they were calculated with the Matlab toolboxes Brain Connectivity Toolbox (Rubinov and Sporns, 2010 a ) and GRETNA (Wang et al, 2015). Mathematical definitions for each metric are presented in Appendix C. We note that the ICC is a commonly used measure designed to assess the similarity of network estimates across scanning sessions (Braun et al, 2012; Choe et al, 2017; Niu et al, 2013), and it is usually derived by calculating the proportion of the total variation attributed to variability across scanning sessions. Thus, small variation across sessions relative to variation between individuals produces high ICC values, indicating strong reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…The network metrics include clustering coefficient, characteristic path length, local efficiency, global efficiency, modularity, hierarchy, and degree, and they were calculated with the Matlab toolboxes Brain Connectivity Toolbox (Rubinov and Sporns, 2010 a ) and GRETNA (Wang et al, 2015). Mathematical definitions for each metric are presented in Appendix C. We note that the ICC is a commonly used measure designed to assess the similarity of network estimates across scanning sessions (Braun et al, 2012; Choe et al, 2017; Niu et al, 2013), and it is usually derived by calculating the proportion of the total variation attributed to variability across scanning sessions. Thus, small variation across sessions relative to variation between individuals produces high ICC values, indicating strong reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…For instance,Zhang et al, 2018 analyzed the reliability of both static FC and dynamic fluctuations (standard deviation, amplitude of low frequency fluctuations, and excursions) in a large population of adults (820 subjects from Human Connectome Project). They found the variations of connectivity dynamics were most robust when the sliding-window length was less than 40 s. However,Choe et al (2017) found, although the temporal features of connectivity dynamics were reliably reproducible, their dFC parameters of connectivity states (number of state transitions and dwell time) had poorer reliabilities across the sliding windows, taped sliding window, and dynamic conditional correlations approach. Thus, our results are informative to demonstrate the robustness of dFC properties in terms of their reproducibility during RW conditions across numbers of clusters or sliding-window lengths.…”
mentioning
confidence: 99%
“…The occurrence of these states predicted inter-subjects' behavioral lapsing and intra-subjects' response speeds (Patanaik et al, 2018;Yeo, Tandi, & Chee, 2015). However, several studies (Choe et al, 2017;Zhang, Baum, Adduru, Biswal, & Michael, 2018) debated the low replicabilities of both temporal brain fluctuations and their dFC parameters across sliding windows using some large samples of public datasets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…constructed biologically-plausible models that are not constrained by individual-level 23 human brain activity or used data-driven statistical characterizations of individuals that are 24 not mechanistic. We aim to bridge this gap through the development of a new modeling 25 approach termed Mesoscale Individualized Neurodynamic (MINDy) modeling, wherein 26 we fit nonlinear dynamical systems models directly to human brain imaging data. The 27 MINDy framework is able to produce these data-driven network models for hundreds to 28 thousands of interacting brain regions in just 1-3 minutes per subject.…”
mentioning
confidence: 99%